Seeking HELP beyond the pill: Women’s perceptions of informed consent for medication abortion: Mixed methods research - Maka Tsulukidze; Gabriele Di Cicco; Tessa Longbons Cox; Katherine A. Rafferty; Stuart W. Grande; Ingrid Skop; David Collison (PLoS ONE, 2026)
Informed consent is a cornerstone of patient autonomy, yet its implementation in medication abortion, especially in the context of rapidly expanding telehealth and online access, remains understudied. This study explores how informed consent is experienced by women who undergo medication abortion, focusing on the information they receive and the gaps they perceive. Using an exploratory sequential mixed methods design, we first conducted a thematic analysis of online narratives to examine how women described their experiences with information, support, and uncertainty. We then developed and administered a national survey informed by these findings to assess how women perceive the informed consent process. Thematic analysis of online narratives revealed four key patterns: women sought information about medication abortion symptoms and side effects; emotional support; urgent reassurance during the process; and clarification of the information provided. Survey results showed that concerns about fetal remains, emotional well-being, and the risk of an incomplete abortion (retained tissue) were strongly associated with women’s sense of being informed. Emotional responses also shaped these perceptions, where women who felt stressed were less likely to feel adequately informed, while those women who felt happy were more likely to report receiving sufficient information. Integration of qualitative and quantitative findings revealed consistent concerns, particularly about unanticipated symptoms, emotional distress, and the need for clearer guidance. Our results suggest that some women experience uncertainty or unmet informational needs prior to taking abortion medications, regardless of care setting. This informational gap raises the possibility of preference misalignment, whereby patients’ expectations may not fully reflect their lived experience. The findings highlight a pressing need for clearer, more comprehensive, and emotionally supportive consent practices, particularly as medication abortion becomes increasingly accessible and utilized by women. Addressing these gaps can strengthen patient-centered care and ensure that women’s choices are informed, respected, and aligned with their values.